LOGIKA DAN METODE PENALARAN DALAM PERSPEKTIF FILSAFAT NYĀYA DARŚANA - Siswadi, Gede Agus (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2022)
Nyāya is one of the Indian philosophical systems belonging to the Astika group. The Nyāya specializes in the exposition of a reasoning methodology or a method used for validation. The validation method in the nyāya philosophical system is called pramana so that the nyāya is very synonymous with the logical system. This study focuses on using a literature study research approach. The results in this study are that there are four principles that need to be carried out in a reasoning or logic in finding a truth, namely, Pratyaksa Pramāna which means a truth obtained through direct observation. Anumāna Pramāna means the truth that is revealed through a process of inference, then Upamāna Pramāna that is revealing the truth through comparison, and finally Sabda Pramāna that is obtaining a truth through witness. The four methods can be used simultaneously to obtain a valid truth.